1986
DOI: 10.1021/bi00357a002
|View full text |Cite
|
Sign up to set email alerts
|

Specific overproduction and purification of the cytochrome b558 component of the cytochrome d complex from Escherichia coli

Abstract: In Escherichia coli strain GR84N[pNG10], the cloned gene for subunit I of the membrane-bound cytochrome d complex resulted in the overproduction of cytochrome b558 and facilitated purification of this cytochrome. Extracting membranes with 1% Triton X-100 followed by two chromatographic steps yielded a single band on sodium dodecyl sulfate-polyacrylamide gels corresponding to subunit I (Mr 57 000). Purified cytochrome b558 was in its native state as determined by difference absorption spectroscopy and by potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 10 publications
0
47
0
Order By: Relevance
“…Cells containing pNG2, the pBR322-derived plasmid with the cloned cyd operon (17), are bright green because of the heme d component in the overproduced oxidase. Cells containing pNG10 are red since they only produce subunit I, which is the cytochrome b558 component of the oxidase (18). About 40% of the plasmids did not overexpress cytochrome and were not characterized further.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells containing pNG2, the pBR322-derived plasmid with the cloned cyd operon (17), are bright green because of the heme d component in the overproduced oxidase. Cells containing pNG10 are red since they only produce subunit I, which is the cytochrome b558 component of the oxidase (18). About 40% of the plasmids did not overexpress cytochrome and were not characterized further.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, cells were grown in 1.5 ml of LB-glucose plus 10 ,ug of tetracycline per ml for 12 to 24 h before harvest. After isolation, plasmids were resuspended in 20 ,ul of 10 mM Tris-HCl (Sigma)-1 mM EDTA (Sigma) (pH 8), and 15 ,ul was used to transform GR84N or G0102.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three of the heme prosthetic groups are located on the periplasmic side of the membrane. Heme b 558 is known to be located entirely within subunit I (Green et al 1984). The Q-loop in subunit I has been suggested to participate in the binding of heme d and subunit II is necessary to bind heme b 595 and heme d in E. coli (Green et al 1984(Green et al , 1986.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence identified showed 85% identity to that of the E. coli cydA gene (14), which codes for subunit I of the cytochrome d oxidase, and indicated that the TnphoA gene had inserted immediately after nucleotide 1478 of the putative S. typhimurium cydA ORF. E. coli cyd mutants show increased sensitivity to sodium azide and hydrogen peroxide, and they produce colonies that are the same size as those of the wild type when grown at 30°C but produce microcolonies at 37°C on L agar (15,31). Mutant GM129 showed an increased sensitivity to sodium azide, but not to hydrogen peroxide, and produced smaller colonies at 30, 37, and 42°C on L agar than those produced by the parent.…”
mentioning
confidence: 99%